Periodontal treatment with a low-level diode laser: clinical findings - Angelov N; Pesevska S; Nakova M; Gjorgoski I; Ivanovski K; Angelova D; Hoffmann O; Andreana S (My University, 2009)
This study assessed the effects of low-level laser treatment in combination with scaling and root planing (SRP) in patients with periodontitis. Sixty subjects with chronic advanced periodontitis were assigned randomly to three treatment groups (n = 20) after collecting gingival clinical parameters. Group A received SRP on a single quadrant per day for four consecutive days; on the fifth day, all quadrants were rescaled. Group B received the same treatment as Group A, followed by laser application for five days. Group C received the same treatment as Group B but the laser treatment was administered for a total of 10 days. For Groups B and C, a low-level diode laser (630 to 670 nm) was used. The plaque index, gingival index, and sulcular bleeding index were recorded for all groups. For all clinical parameters, all three groups reported statistically significant differences (p < 0.005) compared to baseline data. Compared to Group A, Groups B and C showed statistically significant improvement for all clinical parameters. These findings suggest that a low-level diode laser can have a beneficial effect for treating inflammatory chronic advanced periodontitis.